Diffraction radiation interference pattern obtained upon electron beam propagation through a slit target; Journal of Surface Investigation. X-ray, Synchrotron and Neutron Techniques; Vol. 7, Iss. 4 - Shkitov D. A. Dmitriy Andreevich; Naumenko G. A. Gennadiy Andreevich; Shevelev M. V. Mihail Viktorovich; Potylitsyn A. P. Alexander Petrovich; Deng H.; Wang X. (2013, 2013)
Title screen